Um modelo de avaliação interna para a melhoria de processos pedagógicos e administrativo: aplicação em uma faculdade de tecnologia - Freitas, Renata de Castro Marcondes de [UNESP] (2015)
Currently the quality of services and products is considered an important factor in the creation, development and maintenance of a continuous improvement in both the individual and institutional aspect. Given the importance of achieving such quality, this work aimed to develop and validate an institutional / internal evaluation model according to the needs and reality of a college of technology, taking into account the guidelines required by the MEC, the requirements of Evaluation System Institutional - SAI and 10 dimensions established by the Higher Education Evaluation System - SINAES. This work was based on bibliographic, documentary research and case study for the collection of information, analysis of existing evaluation models, so as to develop and implement the institutional assessment model / internal technology college. With a qualitative approach, we applied questionnaires on two occasions. The first time was divided into three phases: application and validation of the proposed model of evaluation, identification of best practices in relation to the evaluation and identification and understanding of faculty vision of the process involving. In the second phase to identify the perception of coordination courses for two evaluation processes: the institutional evaluation process (external) Novo WebSAI and institutional / internal evaluation process (proposed model). Thus, we sought to identify the points at which the institution under study can improve and how these elements can help with suggestions for the internal assessment can become better, faster, more reliable and can add value both for faculty and for the institution itself